Coordination Symmetry Breaking of Single‐Atom Catalysts for Robust and Efficient Nitrate Electroreduction to Ammonia - Cheng, Xue‐Feng; He, Jing‐Hui; Ji, Hao‐Qing; Zhang, Hao‐Yu; Cao, Qiang; Sun, Wu‐Ji; Yan, Cheng‐Lin; Lu, Jian‐Mei (Advanced materials (Weinheim), 2022)
Nitrate electrocatalytic reduction (NO3RR) for ammonia production is a promising strategy to close the N‐cycle from nitration contamination, as well as an alternative to the Haber–Bosch process with less energy consumption and carbon dioxide release. However, current long‐term stability of NO3RR catalysts is usually tens of hours, far from the requirements for industrialization. Here, symmetry‐broken Cusingle‐atom catalysts are designed, and the catalytic activity is retained after operation for more than 2000 h, while an average ammonia production rate of 27.84 mg h−1 cm−2 at an industrial level current density of 366 mA cm−2 is achieved, obtaining a good balance between catalytic activity and long‐term stability. Coordination symmetry breaking is achieved by embedding one Cu atom in graphene nanosheets with two N and two O atoms in the cis‐configuration, effectively lowering the coordination symmetry, rendering the active site more polar, and accumulating more NO3− near the electrocatalyst surface. Additionally, the cis‐coordination splits the Cu 3d orbitals, which generates an orbital‐symmetry‐matched π‐complex of the key intermediate *ONH and reduces the energy barrier, compared with the σ‐complex generated with other catalysts. These results reveal the critical role of coordination symmetry in single‐atom catalysts, prompting the design of more coordination‐symmetry‐broken electrocatalysts toward possible industrialization. A coordination‐symmetry‐breaking Cusingle‐atom catalyst enables a good balance between catalytic activity and long‐term stability in nitrate electroreduction to ammonia. The catalytic activity is retained after operation for more than 2000 h, while an average ammonia production rate of 27.84 mg h−1 cm−2 at an industrial level current density of 366 mA cm−2 is achieved.